Higher Dietary Inflammatory Index Scores Are Associated With Higher Concentrations of Inflammatory Markers in the Framingham Heart Study. (7th June 2021) - van Lent, Debora Melo; Gokingco, Hannah; Benjamin, Emelia; Vasan, Ramachandran; Jacques, Paul; Beiser, Alexa; Seshadri, Sudha; Jacob, Mini; Himali, Jayandra
Abstract: Objectives: We evaluated whether higher (i.e., pro-inflammatory) Dietary Inflammatory Index (DII) scores were associated with increased concentrations of inflammatory markers in the community-based Framingham Heart Study (FHS) Offspring Cohort. Methods: We studied 1978 participants (age 61 [SD, 9] years, 53.9% women) from the Offspring cohort who completed a validated 126-item Food Frequency Questionnaire (FFQ) at exam 7 (1998–2001) and at least one of exams 5 (1991–1995) or exam 6 (1995–1998), and on whom inflammatory markers were measured at exam 7. We created a DII score based on the published scoring algorithm by Shivappa et al. 2014, (developed from previous studies linking individual dietary factors to six inflammatory markers); a cumulative DII score was calculated by averaging across a maximum of three FFQs. We used linear regression models to test associations between the cumulative DII score and natural log-transformed concentrations of adiponectin, cluster of differentiation 40 (CD40), C-reactive protein (CRP), fibrinogen, intracellular adhesion molecule (ICAM), interleukin (IL)-6, IL-18, resistin, and TNF-α. Results: Higher DII scores were independently associated with higher mean concentrations of four inflammatory markers after adjustment for demographic, clinical, and lifestyle covariates (β± SE, CRP 0.14 mg/L ± 0.04; P < 0.0001, IL-6 0.07 pg/mL ± 0.02; P < 0.003, resistin 0.04 ng/mL ± 0.02 ng/mL; P = 0.01). Exclusion of individuals who smoke currently did not change the results. Additionally, we observed that body mass index had a partially mediating effect on all relationships except the relationships with TNF-α. Further, we observed no significant interactions between higher DII scores and sex in their associations with each inflammatory marker. Conclusions: Higher DII scores were associated with higher concentrations of four out of nine inflammatory markers. Our results suggest that anti-inflammatory diets, which correlate with low DII scores may lower systemic chronic inflammation, a process that plays an important role in the development and progression of chronic disease. Funding Sources: ASPEN Rhoads Research Foundation and NIH.